mTOR inhibition by TAK‐228 is effective against growth, survival and angiogenesis in preclinical retinoblastoma models - Lanlan Tang; Yu Fu; Jiarun Song; Taibing Hu; Kun Li; Zhi Li (Wiley, 2022)
Abstract We and others have shown that aberrant activation of the mammalian target of rapamycin (mTOR) signalling is essential for retinoblastoma progression and has potential therapeutic value. TAK‐228 is a potent inhibitor of mTOR1 and 2 with preclinical activity in a variety of cancers. In this study, we report that TAK‐228 is a dual inhibitor of retinoblastoma and angiogenesis. TAK‐228 inhibits growth and induces apoptosis in a panel of retinoblastoma cell lines, with IC50 at ~0.2 μM. Under the same experimental conditions, TAK‐228 was less effective in inhibiting growth and survival in normal retinal and fibroblast cells than retinoblastoma cells. In addition, TAK‐228 inhibited retinal endothelial cell capillary network formation, migration, growth and survival. We further demonstrate that TAK‐228 inhibits retinoblastoma and retinal angiogenesis through inhibiting mTOR signalling. Rescue studies confirm that mTOR is the target of TAK‐228 in both retinoblastoma and retinal endothelial cells. Finally, we confirm the inhibitory effects of TAK‐228 on tumor and angiogenesis in retinoblastoma xenograft mouse model. Our findings provide a preclinical rationale to explore TAK‐228 as a strategy to treat retinoblastoma and highlight the therapeutic value of targeting mTOR in retinoblastoma.